Mental health and the role of social support in the lives of vulnerabilized sexual minority women - Jennifer L. Glick; Megan G. Nguyen; Aimee K. Huang; Kamila A. Alexander; Danielle German (PLoS ONE, 2025)
Introduction Sexual minority women (SMW; women who self-identify as lesbian, queer, etc., as well as heterosexually-identified women who experience attraction to romantic or sexual partnerships with women) and vulnerabilized women (those marginalized due to structural forces such as housing insecurity, violence, sex exchange, drug use, or HIV positive status) experience a range of mental health challenges compared to their heterosexual and general population counterparts. General populations studies show a positive relationship between social support and mental health; less is known about SMW experiencing intersecting multi-layered vulnerabilities. This study characterizes mental health stressors, identifies social support sources and forms, and explores the relationship between social support and mental health among vulnerabilized SMW in Baltimore, MD. Methods We conducted virtual, in-depth semi-structured interviews with vulnerabilized cisgender SMW (n = 25) between June and October 2021. We utilized an inductive analytical approach to identify central themes and develop a categorization structure. Results are presented using narrative synthesis and illustrative quotes. To understand different forms of mental health-related social support provided across sources, data was sorted into a matrix and analyzed. Results Vulnerabilized SMW commonly self-reported depression and anxiety. Participants identified three primary mental health stressors: 1) managing identity-related stigma; 2) relationships, loss, and isolation; and 3) financial struggles. The most important type of social support for mental health was non-judgement related to sexual orientation and/or mental health struggles. Family, friends, and partners were providing similar amounts of support, primarily emotional support. Discussion Vulnerabilized SMW have unique mental health and social support-related experiences and needs, potentially attributed to experiences with multiple marginalization, compounded by struggles with intersecting structural vulnerabilities. More research is warranted to explore different sources and forms of social support as predictors of mental health. Findings indicate need for public health interventions that address sexual orientation and mental health stigma.